Prínos hyperbaroxie v lécbĕ nekrotizující fasciitidy - Krásová, Z; Matusek, A; Chmelar, D (Vnitrni lekarstvi, 1992)
The authors present the results of treatment provided to 11 patients with necrotizing fasciitis who were after a surgical operation and after administration of antibiotics treated in a hyperbaric chamber. A total of 8 patients (82%) recovered completely. The authors discuss the theory of action of hyperbaric oxygen on microorganisms and draw attention to the possible reduction of mortality of this serious disease when using hyperbaric oxygenation. The latter is considered an important auxiliary method which supplements surgical treatment, rational antibiotic therapy and in particular careful intensive care.
Keywords: Child; Female; Adult; dospělí; Hyperbaric Oxygenation; fasciitida; Humans; ženské pohlaví; Fasciitis; mužské pohlaví; Male; lidé; Necrosis; hyperbarická oxygenace; dítě; nekróza